Culture and education - Qvarsell, Birgitta; Wulf, Christoph, 1944- (Waxmann, 2003)
Although the educational system still fulfills the task of anchoring young generations within the national cultures that make up Europe, the progressive loss of significance of national states, which is connected to the process of unification and globalization, is creating new challenges to the various European cultures and to the education systems embodied in their people. Cultures are sustained and transformed through the manner in which they communicate with the younger generation; it is at this level that they constitute their particular power and dynamic
Keywords: pedagogická antropologie -- Evropa; vzdělávání -- Evropa; vzdělávání -- sociální aspekty -- Evropa; educational anthropology -- Europe; education -- Europe; education -- social aspects -- Europe; sborníky; papers of several authors